Academic Problems at College of Education- Girls' Section in Hail University, from Students & Staff Members Perspectives - Salaheldin Farah Attallah Bakhiet; Hibat Allah Muhammad Elhassan Salim (University of Science and Technology, Yemen, 2016)
Abstract:     This study aims at investigating the academic problems at college of education- girls'  section, from students & staff Members perspectives. A strata random sample consisted of (329) participants, on which (229) student , and (90) college  members were chosen.     For data collection, Academic Problems Scale prepared by the researchers was used. The most remarkable findings are:   There are significant differences in estimating the severity of academic problems ,between students and staff members , for students benefit, and the presence of a 50% difference in the ranking of the severity of the problems between the two groups. Other results were: - From the perspective of the students the problems of the educational process and organization are the most frequent problems, followed by problems with the availability and adequacy of support services, then the counseling and guidance of university problems, the problems of student motivation and interest, and finally issues related to college  members. - From the point view of the college  members,  provide support and adequacy services is the most frequent problems, followed by problems with student motivation and interest, then the problems of the implementation of the educational process and organization, the counseling and guidance, and finally issues related to faculty members. - There are significant differences in estimating the severity of the academic problems, between students of the kindergarten department and those of home economic , for the benefit of the first. - There are no significant differences between students in estimating the academic problems attributed to their academic levels. - There is no significant  correlation between students , in estimating the academic problems ,& their academic GPA -- There is no significant differences between staff members, in estimating the academic problems, according to their academic ranks - There is no significant differences between staff members , in estimating the academic problems ,according to their assigned departments. - There is no significant differences between staff members , in estimating the academic problems ,according to their professional experiences.